Perbedaan Pengetahuan Ibu Hamil Trimester III Sebelum dan Sesudah diberikan Penyuluhan Tentang KB IUD Pasca Plasenta di BPM NY. E Desa Serangan Kecamatan Mlarak Kabupaten Ponorogo - Sumini Sumini (Jurnal Delima Harapan, 2017)
Based on data from East Java Health department (2014) showed thatactive participant of family planning of contraceptive method were 43,4 %, 56,6% didn’t use long term contracpetive method. From active new acceptors 31,7 %used long term contraceptive method, and 68,3 % didn’t use it. Based on thepreliminary in the village Serangan sub district of Mlarak Ponorogo, 4 out of 10respondents were had study by interview good knowledge about contraceptiveIUD Post Placenta and 6 out of 10 respondents were not interest. Problems thathave occurred one mothers have failed in the installation of post plasetal IUDcontraception. The purpose of this study was to determine differences in maternalknowledge about contraceptive before and after counseling about IUD PostPlasenta in BPM NY E Serangan village Mlarak, Ponorogo.The type of research was one group pre post test design. The samplingtechnique was Total sampling. Research intruments Questionnaire. Population ofthis research intruments 30 third trimester pregnant women. With a total sampleof 30 respondents. Research condueted in January 18 – 28 days, variable ofresearch was independent variables and date analyzed by paired T– test.The result of the research before the counseling of 30 respondents get 21most respondents ( 70% ) had less knowledge cathegory, while knowledge aftermost 21 respondents ( 70 % ) had enough cathegory. Ha test statistic test isaccepted when ρ < 0,05. It can be concluded 0,000 < 0,05. That is, there isdifference knowledge of pregnant mother of trimester III before and after givencounseling about IUD Post Placenta at BPM NY “ E” Serangan village subdistrict Mlarak regency Ponorogo.It is expected that the results of this study can be used to be input forhealth workers, especially in BPM Ny “ E” Serangan villages to support trimesterpregnant women III by providing counseling related to post placental IUDcontraceptives.